1994
DOI: 10.2115/fiber.50.4_175
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Dyeing of Silk Using a Redox System.

Abstract: The mechanism of improvement in exhaustion and fixation of acid dyes in the recently reported low-temperature dyeing of silk fabrics with acid dyes in the presence of a hydrogen peroxide/glucose redox system was studied. The increases in dyeing rate and adsorption of acid dyes on silk fibers in the presence of the redox system could be attributed to the decrease in pH due to the decomposition of glucose with hydrogen peroxide but not to the covalent fixation of dyes on silk assisted by the free radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Results of the study showed that exhaustion and fixation of acid dyes improved because of the increase in the number of dye sites through the action of free radicals, assisting in covalent fixation. The mechanism of improvement in exhaustion and fixation of acid dyes using the above redox system was attributed to the decrease in pH of the dye solution as a result of the decomposition of glucose with hydrogen peroxide 10…”
Section: Introductionmentioning
confidence: 99%
“…Results of the study showed that exhaustion and fixation of acid dyes improved because of the increase in the number of dye sites through the action of free radicals, assisting in covalent fixation. The mechanism of improvement in exhaustion and fixation of acid dyes using the above redox system was attributed to the decrease in pH of the dye solution as a result of the decomposition of glucose with hydrogen peroxide 10…”
Section: Introductionmentioning
confidence: 99%
“…Similar results in low temperature dyeing of silk with acid dyes in the presence of redox systems has also indicated the absence of covalent bond fixation. 19 …”
Section: Effect Of Go/spi and Go/aps Redox Systems Concentrationmentioning
confidence: 99%